(untitled) (Journal of Partial Differential Equations, 2019)
" In this paper, we study a hyperbolic type chemotaxis model in one space dimension. We assume the speed is constant, the production and degradation of the external signal s is given by mbox- beta s+f(u^++u^-), where f(u^++u^-) is the general form and u^+, u^- depend on s. The existence of the weak solution of the model considered in the paper is obtained by00a0 the method of characteristics and the contraction mapping principle."